Filtering method of nano SiC powder

By using nano SiC powder filtering method in the field of electrostatic chucks, membrane filtration is performed using precursors and multi-layer stainless steel filters to optimize the particle size distribution of nano silicon carbide powder, solving the problem of easy precipitation of nano powder slurry and large particles forming, and achieving improved electrical performance of ceramic dielectric layer and breakdown protection of electrostatic chuck.

CN119565267APending Publication Date: 2025-03-07JUNYUAN ELECTRONIC TECHNOLOGY (HAINING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411620180.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the field of electrostatic chucks, the slurries prepared by nano powders are prone to precipitation and agglomeration, resulting in a decrease in the dielectric strength and voltage resistance of the ceramic dielectric layer. In addition, large-grain ceramic powders are prone to form pores during the sintering process, reducing the overall strength and toughness of the material and increasing the risk of breakdown.

Method used

A nano SiC powder filtering method is adopted, through the preparation of precursors and the preparation of slurry, combined with a membrane filtration system of multi-layer stainless steel filter mesh, low-pressure dead-end filtration or cross-flow filtration is carried out to optimize the particle size distribution of nano silicon carbide powder, eliminate large particles, and improve the viscosity adjustment of slurry.

Benefits of technology

The electrical performance of the ceramic dielectric layer prepared by nanoceramic powder is achieved, preventing the electrostatic chuck from being broken down during use, reducing the presence of large particles of the ceramic matrix after sintering, and improving the overall strength and toughness of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565267A_ABST
    Figure CN119565267A_ABST
Patent Text Reader

Abstract

The invention discloses a filtering method of nano SiC powder, and belongs to the technical field of electrostatic chucks, the filtering method comprises the following steps: preparing a precursor; preparing slurry: adding 100 parts of nano silicon carbide powder, a proper amount of dispersing agent, a proper amount of solvent and a proper amount of ball into a planetary mill, running at the speed of 400rpm / min for at least 1 hour, standing for 15 minutes, adding the precursor with the proportion of 3%-9%, and stirring at the speed of 400rpm / min for at least 30 minutes; filtering: filtering is carried out through a filtering device, the filtering device comprises a pressure tank, stable slurry obtained through treatment of nano silicon carbide is loaded into the pressure tank, the slurry is extruded into a membrane filtering system through nitrogen extrusion, and subsequent starting is facilitated through collection of discharged materials and nitrogen storage; and the membrane filtration system adopts a multi-layer stainless steel filter screen or a RoKi PP organic membrane or a hollow fiber ceramic membrane as a filter medium of the nano silicon carbide slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for filtering nano SiC powder. Background Art

[0002] The relationship between the particle size and strength of ceramic materials is generally that as the particle size decreases, the strength index increases. Nano-ceramic powder can cause the size of the material's grains and internal pores or defects to decrease. Small grains are less likely to cause transgranular fracture, which is beneficial to improving the fracture toughness of the material.

[0003] Under the action of an electric field, the process of breakdown caused by defects inside a ceramic part mainly involves the following steps:

[0004] (1) Electric field concentration: Defects inside ceramic parts, such as pores, microcracks or other inhomogeneities, will cause the electric field to concentrate in these areas. This is because in a homogeneous medium, the electric field lines are evenly distributed, but at defects, the electric field lines will bend and concentrate, resulting in a significant increase in the local electric field strength.

[0005] (2) Electrical breakdown: When the local electric field strength exceeds the electrical breakdown strength of the ceramic material, the insulation performance at the defect will drop sharply. Under the action of the electric field, the air or ceramic material at the defect will be ionized to form a conductive path. This process is called electrical breakdown. The occurrence of electrical breakdown is usually accompanied by a sharp increase in current, because the formation of the conductive path significantly reduces the resistance of the ceramic material.

[0006] (3) Thermal effect: During the electrical breakdown process, the sharp increase in current will cause the local temperature to rise rapidly. High temperature will further expand the defects and accelerate the degradation of ceramic materials. The accumulation of heat may lead to thermal breakdown of ceramic materials, that is, the destruction of material structure and loss of insulation properties due to excessive temperature.

[0007] (4) Breakdown extension: Once electrical breakdown occurs, the conductive channels formed will expand rapidly because more heat will be generated when current passes through these channels, further exacerbating the damage to the material. The expansion of the breakdown channel will cause the insulation properties of the ceramic part to be completely lost, and eventually the entire ceramic part will be broken down.

[0008] In the field of electrostatic chucks, ceramic powders are the core raw materials for the preparation of precision semiconductor components. The uniformity of their particle size distribution affects the effects of subsequent casting and printing processes, resulting in a significant reduction in the dielectric strength and pressure resistance of the prepared electrostatic chuck ceramic dielectric layer, which is not conducive to wafer processing. In particular, if the slurry prepared by nanopowders is easy to precipitate and agglomerate, the compactness and stability of the ceramic medium will be affected; the particle size of the ceramic powder in the ceramic slurry will affect the thickness of the dielectric layer, and large particles of ceramic powder are prone to form larger pores during sintering, because the gaps between large particles are difficult to be completely filled during the sintering process. These pores will become stress concentration points, reducing the overall strength and toughness of the material. When larger powder particles are sintered, incomplete or uneven sintering may occur, resulting in internal stress and microcracks, which will weaken the mechanical strength of the material. In addition, the most important point is that when the electrostatic chuck is working, the gaps between the large particles of the ceramic dielectric layer will become breakdown points, releasing charges and local heat to the outside, causing the electrostatic chuck to explode due to insufficient local pressure resistance. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a method for filtering nano SiC powder, optimize the particle size distribution of nano silicon carbide powder, stabilize the slurry casting and printing processes after filtration, and greatly reduce the presence of large particles in the ceramic matrix after sintering, which leads to a decrease in the electrical performance of the electrostatic chuck product.

[0010] In order to solve the above technical problems, the technical solution of the present invention is:

[0011] A method for filtering nano-SiC powder, the filtering method comprising the following steps:

[0012] Preparation of precursor:

[0013] 100 parts of polymer precursor are added to a mixed solution of toluene and isopropanol, wherein the ratio of toluene to isopropanol is 1:3 to 1:1, and then 60 parts of plasticizer DBP are added, and stirred at high speed for 2 hours at a temperature of 25°C to allow the organic resin to fully swell and dissolve. After it is completely dissolved, it is allowed to stand for 24 hours for use;

[0014] Preparation of slurry:

[0015] Add 100 parts of nano silicon carbide powder, appropriate amount of dispersant, solvent and ball into the planetary mill, run at 400 rpm / min for at least 1 hour, let it stand for 15 minutes, then add the above precursor, the ratio of the precursor is 3% to 9%, and stir at 400 rpm / min for at least 30 minutes, then test the viscosity and temperature of the slurry, and add a small amount of precursor to continue stirring. The specific amount added is adjusted according to the actual process;

[0016] filter:

[0017] The filtration is carried out through a filtration device, which includes a pressure tank. The stable slurry obtained by the nano-silicon carbide treatment is loaded into the pressure tank, and the slurry is squeezed into the membrane filtration system through nitrogen extrusion. The output is collected and stored with nitrogen for subsequent activation. The membrane filtration system uses multi-layer stainless steel filter mesh or RoKi PP organic membrane or hollow fiber ceramic membrane as the filtration medium for nano-silicon carbide slurry.

[0018] Preferably, the filtering device comprises a nitrogen device, the nitrogen device is connected to the pressure tank through a pipeline, and the pipeline is provided with a main valve and a pressure control valve.

[0019] Preferably, the filter medium is a multi-layer stainless steel filter mesh.

[0020] Preferably, the multi-layer stainless steel filter screen includes five layers of filter screen sheets.

[0021] Preferably, the filtering method is: dead-end filtration at a low pressure of 0.1 to 0.2 MPa, or multiple cycles of filtration by cross-flow filtration.

[0022] Preferably, the viscosity of the slurry is less than 100 cp.

[0023] The above technical solution has the following beneficial effects:

[0024] (1) There are various choices of precursors. The corresponding precursors can be selected according to the density, particle size and specific surface area of ​​the nanopowder. The precursors wrap the ceramic particles so that they are evenly screened during filtration, thus achieving the effect of eliminating large particles;

[0025] (2) The viscosity of the slurry is highly adjustable, which makes the flux and efficiency higher during the filtration process. In addition, the stainless steel multi-layer sintered filter mesh is designed to maintain high filtration efficiency and significantly reduce the processing cost;

[0026] (3) The ceramic dielectric layer prepared by the filtered nano-ceramic powder has better electrical properties, preventing the electrostatic chuck from being broken down during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic structural diagram of the filtering device of the present invention. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0029] A method for filtering nano-SiC powder, the filtering method comprising the following steps:

[0030] Preparation of precursor:

[0031] 100 parts of polymer precursor are added to a mixed solution of toluene and isopropanol, wherein the ratio of toluene to isopropanol is 1:3 to 1:1. In other embodiments of the present embodiment, the ratio of toluene to isopropanol is 1:3 or 1:1. In addition, the ratio of toluene to isopropanol can also be 1:2. Then 60 parts of plasticizer DBP are added, and the mixture is stirred at high speed for 2 hours at a temperature of 25°C to fully swell and dissolve the organic resin. After it is completely dissolved, it is allowed to stand for 24 hours for use.

[0032] Organic polymer precursors can be selected from B98 organic resin, which is also called polyvinyl butyral resin. It has unique properties and is widely used in many fields. The corresponding small molecule organic matter can be added according to the casting system to facilitate subsequent debonding.

[0033] Preparation of slurry:

[0034] 100 parts of nano silicon carbide powder, an appropriate amount of dispersant, solvent and ball are added to the planetary mill, and the mill is run at a speed of 400 rpm / min for at least 1 hour. After standing for 15 minutes, the above-mentioned precursor is added, and the proportion of the precursor is 3% to 9%. In other embodiments of the present embodiment, the proportion of the precursor is 3% or 9%. In addition, the proportion of the precursor can also be 6%. After adding the precursor, stir at a speed of 400 rpm / min for at least 30 minutes, and then test the viscosity and temperature of the slurry. According to the test results, a small amount of precursor can be appropriately added and stirred for at least 30 minutes. The specific amount added is adjusted according to the actual process;

[0035] filter:

[0036] refer to Figure 1 , filtering is performed by a filtering device, the filtering device includes a pressure tank 2, the stable slurry obtained by the nano-silicon carbide treatment is loaded into the pressure tank 2, and the slurry is squeezed into the membrane filtration system 3 by nitrogen extrusion, the membrane filtration system 3 includes a support body at both ends and a filter screen in the middle, the discharge is collected by a collector 7 and nitrogen is stored for subsequent activation, and the membrane filtration system 3 uses a multi-layer stainless steel filter screen or a RoKi PP organic membrane or a hollow fiber ceramic membrane as a filter medium for the nano-silicon carbide slurry;

[0037] The purpose of the present invention is to provide a filtering method with excellent performance and low cost, which overcomes the technical problem of low filtering efficiency of traditional nano-ceramic powders, optimizes the particle size distribution of nano-silicon carbide powders through pre-treatment and post-filtration of powders, stabilizes the tape casting and printing processes of nano-ceramic slurries, and greatly reduces the problem of decreased electrical performance of electrostatic chuck products caused by the presence of large particles in the ceramic matrix after sintering. A slurry with low viscosity and uniform composition is obtained by dispersing nano-silicon carbide and stabilizing and suspending organic polymers, so that large particles can be easily screened under low pressure, effectively simplifying the membrane filtration process and reducing the cost of powder processing;

[0038] The filtering device includes a nitrogen device 1, which is connected to a pressure tank 2 through a pipeline 4. A main valve 5 and a pressure control valve 6 are provided on the pipeline 4. The slurry is squeezed into the membrane filtration system 3 for filtration by squeezing the nitrogen device 1. The main valve 5 is used to control opening and closing, and the pressure control valve 6 is used to control the pressure.

[0039] The filter medium is a multi-layer stainless steel filter. Currently, the filter membranes available include inorganic membranes, organic membranes and metal membranes. Hollow fiber ceramic membranes are preferred for inorganic membranes, RoKi PP or PVDF filter membranes are preferred for organic membranes, and sintered multi-layer stainless steel filter membranes are preferred for metal membranes. Sintered stainless steel multi-layer filter membranes are selected from the perspectives of cost and filtration efficiency. The multi-layer stainless steel filter includes five layers of filter mesh.

[0040] The filtration method is: dead-end filtration under low pressure of 0.1-0.2MPa, or multiple cycles of filtration through cross-flow filtration. Since filtration is a dynamic process, in addition to increasing the filtration area and filtration flux, the internal and external resistance of the membrane generated by filtration should also be reduced to improve the membrane filtration efficiency. According to the membrane series resistance model, the membrane pollution resistance is divided into internal and external resistance. The external resistance is mainly concentration polarization Rcp and filter cake layer resistance Rg. The internal pollution resistance is mainly solute adsorption Ra and membrane pore blockage resistance Rp. RoKi organic membrane cannot remove these resistances and is used twice. Hollow fiber ceramic membrane can be used multiple times but the cost is high. Relatively speaking, multi-layer stainless steel filter mesh can be used multiple times and customized with high precision and low cost, and is preferred as the filtration medium of nano silicon carbide.

[0041] The viscosity of the slurry is less than 100cp. Due to the assistance of the organic precursor, the viscosity of the slurry is controllable and can be filtered at a low viscosity (less than 100cp).

[0042] The use of the technical solution of the present application to filter nano-silicon carbide slurry has the following advantages:

[0043] There are various choices of precursors, and the corresponding precursors can be selected according to the density, particle size and specific surface area of ​​the nanopowder. The precursor wraps the ceramic particles so that they are evenly screened during filtration, achieving the effect of eliminating large particles;

[0044] The viscosity of the slurry is highly adjustable, which makes the filtration process more efficient and has a higher flux. In addition, the stainless steel multi-layer sintered filter mesh is designed to maintain high filtration efficiency while significantly reducing the processing cost.

[0045] The ceramic dielectric layer prepared from the filtered nano-ceramic powder has better electrical properties, preventing the electrostatic chuck from being broken down during use.

[0046] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A method for filtering nano-SiC powder, characterized in that: The filtering method comprises the following steps: Preparation of precursor: 100 parts of polymer precursor are added to a mixed solution of toluene and isopropanol, wherein the ratio of toluene to isopropanol is 1:3 to 1:1, and then 60 parts of plasticizer DBP are added, and stirred at high speed for 2 hours at a temperature of 25°C to allow the organic resin to fully swell and dissolve. After it is completely dissolved, it is allowed to stand for 24 hours for use; Preparation of slurry: Add 100 parts of nano silicon carbide powder, appropriate amount of dispersant, solvent and ball into the planetary mill, run at 400 rpm / min for at least 1 hour, let it stand for 15 minutes, then add the above precursor, the ratio of the precursor is 3% to 9%, and stir at 400 rpm / min for at least 30 minutes, then test the viscosity and temperature of the slurry, and add a small amount of precursor to continue stirring. The specific amount added is adjusted according to the actual process; filter: The filtration is carried out through a filtration device, which includes a pressure tank. The stable slurry obtained by the nano-silicon carbide treatment is loaded into the pressure tank, and the slurry is squeezed into the membrane filtration system through nitrogen extrusion. The output is collected and stored with nitrogen for subsequent activation. The membrane filtration system uses multi-layer stainless steel filter mesh or RoKi PP organic membrane or hollow fiber ceramic membrane as the filtration medium for nano-silicon carbide slurry.

2. The method for filtering nano-SiC powder according to claim 1, characterized in that: The filtering device comprises a nitrogen device, which is connected to a pressure tank through a pipeline, and a main valve and a pressure control valve are arranged on the pipeline.

3. The method for filtering nano-SiC powder according to claim 1, characterized in that: The filter medium is a multi-layer stainless steel filter screen.

4. The method for filtering nano-SiC powder according to claim 3, characterized in that: The multi-layer stainless steel filter screen comprises five layers of filter screen sheets.

5. The method for filtering nano-SiC powder according to claim 1, characterized in that: The filtering method is: dead-end filtering at a low pressure of 0.1-0.2 MPa, or multiple cycle filtering by cross-flow filtration.

6. The method for filtering nano-SiC powder according to claim 1, characterized in that: The viscosity of the slurry is less than 100 cp.